Singapore : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Outlook and risks. Following an upturn in 2013, growth is expected to moderate somewhat during 2014-2015, narrowing the positive output gap. The impact of recovering demand in advanced economies is likely to be offset by the ongoing real appreciation of the currency and the gradual tightening in global monetary conditions. Transitional costs related to the economic restructuring (see next paragraph) are also expected to dampen growth in the near term. As a very open economy, Singapore is particularly exposed to external risks related to a protracted period of slower growth in advanced and emerging economies, a continued buildup and eventual unwinding of excess capacity in China, an abrupt surge in financial market volatility as investors reassess underlying risks, and geopolitical risks. Medium- and long-term challenges. The authorities focus squarely on the implementation of their medium-term economic restructuring plan. With the aim to boost the productivity of labor and land, the plan could set the stage for a new era of sustainable growth. However, productivity improvements may take some time to materialize. For example, the slowing inflow of foreign workers, a key part of the reform agenda, could moderate potential growth and lower competitiveness in light of the tight labor market. The social safety net is being strengthened in the context of a rapidly aging population. Policy assessment. Singapore continues to implement a strong set of macroeconomic and financial sector policies. The moderately tight monetary policy remains appropriate but the fiscal stance is looser than would be warranted by cyclical considerations. The 2014 budget focuses on noncyclical considerations, including support for companies' efforts to raise productivity and additional social spending on healthcare for the elderly. The authorities' plan to raise social and infrastructure spending by 1-2 percent of GDP over the medium term should help reduce the large current account surplus. Financial regulation and supervision is among the best globally and Singapore is a frontrunner in implementing global regulatory reforms. Macroprudential policies have contributed to cool the housing and car permit markets and good progress has been made in implementing key short-term FSAP recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet